Human-Centered Design in Industry: Lessons from the Trenches. - Ardito, Carmelo; Buono, Paolo; Caivano, Danilo; Costabile, Maria Francesca; Lanzilotti, Rosa; Dittrich, Yvonne (Computer (00189162), 2014)
Integration of human-centered design in a company's software development practice requires a thorough analysis of its current practices by both researchers and practitioners.